STRUKTUR PENGUNGKAPAN MODALITAS AJAKAN DALAM BAHASA JEPANG - Kasmawati (Kagami : Jurnal Pendidikan dan Bahasa Jepang, 2019)
Expression in invitation modality in Japanese are appeared by what shown among verb "shiyou, shiyouka, and shinaika". Data used in Japanese is sentences in invitation form in novel which were analyzed based on the theory of modality. The result obtained, in invitation sentence structure characterized by the presence or absence of occurrence personal pronouns in Japanese as indicated by the adverb shiyou, shiyouka, and shinaika that be followed by the first person plural inclusive pronouns.